THE CONTRIBUTION OF QUR'ANIC PSYCHOLOGY TO THE CONCEPT OF MODERN EDUCATIONAL PSYCHOLOGY ISLAMIC EDUCATION PERSPECTIVES - Muhammad Khairan Arif (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2024)
The Qur'an is the main source of religious and social sciences in Islam. The Qur'an was agreed upon by the Islamic scholars, not only discussing the issues of religion and morality, but also giving information and cues about science and science to humans. Among the sciences is the science of psychology, especially the psychology of human development. The purpose of this research is to explore and introduce the concept of developmental psychology in the Qur'an and As-Sunnah in order to be referenced by people who struggle in this field, including educators. The method used in this research is qualitative method with library research approach and descriptive analysis of the findings obtained from the library data. The results of this study explain that the soul in the Qur'an includes several understandings; Soul means Spirit, Soul means man as a whole consisting of spirit and body, Soul means potential human mind, Soul means heart (Qolb) and Soul means potential good and bad. The soul or human psychology has certain types and conditions according to God's creation and the soul or human psychology undergoes 3 (three) stages of development; weak, strong and weak the second.